INHIBITION OF ALPHA-MANNOSIDASES BY 7 CARBON SUGARS - SYNTHESIS OF SOME 7 CARBON ANALOGS OF MANNOFURANOSE - Myerscough, P; Fairbanks, A; Jones, A; Bruce, I; Choi, S; Fleet, G; Aldaher, S; Dibello, I; Winchester, B (1992)
The effects on human liver glycosidases of some seven carbon analogues of mannopyranose and mannofuranose are compared with those of deoxymannojirimycin and DIM. The syntheses of the seven carbon mannofuranose analogues, α-(aminomethyl)-1-deoxy-mannofuranose and of α-homoDIM, are described. © 1992.